Determinants of FDI in developing countries: has globalization changed the rules of the game? - Peter Nunnenkamp (Kiel Institute for World Economics (IfW), 2002)
There is a startling gap between, allegedly, globalization-induced changes in international competition for foreign direct investment (FDI) and recent empirical evidence on the relative importance of determinants of FDI in developing countries. We show that surprisingly little has changed since the late 1980s. Traditional market-related determinants are still dominant factors. Among non-traditional FDI determinants, only the availability of local skills has clearly gained importance. As concerns the interface between trade policy and FDI, we find that the tariff jumping motive for FDI had lost much of its relevance well before globalization became a hotly debated issue.
Keywords: F21; 330; market size; cost factors; human capital; openness to trade; globalization; foreign direct investment; Direktinvestition; Landesgröße; Standortfaktor; Humankapital; Politik der offenen Tür; Globalisierung; Schätzung; Entwicklungsländer